Integration of intellectual, emotional and spiritual intelligence in the Islamic education curriculum: a holistic approach - Mahdee Maduerawa; Hanan Samae; Ikhlas Wae-alee (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This aim research highlights the importance of these three intelligences in the Islamic education curriculum. Intellectual intelligence helps students think critically and understand complex concepts, emotional intelligence allows them to manage emotions and social interactions effectively, while spiritual intelligence provides deep meaning and purpose in life. The research method used is a literature study, by reviewing literature and related journals. The results of the study show that the integration of the three intelligences in the Islamic curriculum can improve the overall quality of education, create an inclusive learning environment, and support the development of students' character. The novelty of this research lies in a holistic approach that combines intellectual, emotional, and spiritual aspects in one integrated curriculum, which has not been widely applied in the context of Islamic education before. This integration not only prepares students for academic success, but also to become thoughtful, empathetic individuals, and have a strong spiritual life, which further contributes positively to society.